Application of Wireless Sensor Network in Monitoring Quality of Irrigation Water - Kien, Hoang Trung; Minh, Hoang Anh; Jeungprasopsuk, Wilasinee (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
One of the things that needs to be considered to maximize the quantity and quality of agricultural products is the maintenance of irrigation water. Farmers still difficult to monitor the quality of irrigation water due to the high cost of laboratory tests and the need for real-time monitoring of water discharge into rice fields. Some of the impacts of not maintaining irrigation water in recent years include the roots rotting easily. This research aims to create a system that can detect and monitor the quality of irrigation water that will flow into rice fields according to water quality criteria in real time with wireless sensor network technology. In this research, the parameters of pH, conductivity, temperature, and dissolved oxygen are used to determine the quality of irrigation water quality. Based on the experiment results of two types of irrigation water; river water has good pH and conductivity values while the value of dissolved oxygen is poor, while borehole water has good pH, conductivity, and dissolved oxygen values. The calibration process was carried out under the procedures and succeeded well, characterized by sensors that can detect the quality value of irrigation water. In this research, the data from the sensors can be transferred to the server via the GSM module with a time difference between data of about 10-40 seconds. This indicates the performance of the sensor and detection system is running well.